Promoting Real-World Interpreting Skills through Authentic Assessment in Tertiary Education - Setiawan, Anjar; Eka Budiastuti, Riana (LPPM Universitas Pancasakti Tegal, 2025)
This study investigates the effectiveness of authentic assessment in promoting real world interpreting skills among 42 undergraduate students enrolled in the Simple Interpreting course at the English Education Study Program of Universitas Muhammadiyah Semarang. Because interpreting requires spontaneous processing, contextual reasoning, accuracy, and clear delivery, this research examines how authentic performance tasks including simulated dialogues, role play interpreting, and real time scenario-based activities enhance students’ interpreting competence. Using a mixed methods design, the study combines quantitative pre and post assessments with qualitative reflections, interviews, and classroom observations. The quantitative results show substantial improvement in fluency, accuracy, comprehension, and delivery, with an overall mean gain of 13.76 points, indicating significant progress across all indicators. The qualitative findings reveal that authentic assessment fosters greater confidence, strategic adaptability, cognitive awareness, and professional readiness as students engage with the unpredictability and complexity of real interpreting contexts. Triangulated evidence from multiple data sources confirms that authentic assessment not only improves measurable performance outcomes but also strengthens learners’ ability to manage real time communicative demands. The study highlights the pedagogical value of integrating authentic assessment into interpreting instruction and provides implications for curriculum development aimed at preparing students for authentic professional interpreting practices. Thus, this study offers several beneficial insights for future research.